Discordance in prediction of prognosis among patients with intrahepatic cholangiocarcinoma: A preoperative vs postoperative perspective. Issue 6 (13th August 2019) - Moro, Amika; Paredes, Anghela Z.; Farooq, Ayesha; Sahara, Kota; Tsilimigras, Diamantis I.; Mehta, Rittal; Endo, Itaru; Guglielmi, Alfredo; Aldrighetti, Luca; Alexandrescu, Sorin; Marques, Hugo P.; Shen, Feng; et al.
Abstract: Background: The objective of the current study was to characterize patients with intrahepatic cholangiocarcinoma (ICC) undergoing curative‐intent surgery with discordant preoperative and postoperative prediction scores and determine factors associated with prediction discrepancy. Methods: Patients who underwent hepatectomy for ICC between 1990 and 2016 were identified in a multi‐institutional international database. Preoperative and postoperative prognostic models were designed and discordant prognostic scores were identified. A multivariable logistic regression analysis was completed to determined factors associated with score discordance. Results: Among 1149 patients, those who had concordant prediction scores were older (median age, 60 vs 56), and more likely to have a smaller median tumor size (6.0 vs 7.5 cm) (all P < .05). On multivariable logistic analysis, patients with higher neutrophil‐lymphocyte ratio (odds ratio [OR], 1.14; 95% confidence interval [CI], 1.09‐1.19), higher CEA levels (OR, 1.25; 95% CI, 1.04‐1.50), larger tumors (OR, 1.10; 95% CI, 1.04‐1.15) and suspicious lymph nodes (OR, 2.05; 95% CI, 1.25‐3.36) were more likely to have preoperative and postoperative score discordance. Older patients had decreased odds of having score discordance (OR, 0.98; 95% CI, 0.96‐0.99). Patients with score discordance had worse overall survival compared with patients with concordant scores (median:15.9 vs 21.7 months, P < .05). Conclusion: Score discordance may reflect an aggressive variant of ICC that would benefit from early integration of multidisciplinary treatment strategies.